Experimental hypertension triggers varicosis-like maladaptive venous remodeling through activator protein-1 - Feldner, Anja; Otto, Hannes; Rewerk, Stephan; Hecker, Markus; Korff, Thomas (The FASEB journal, 2011)
An increase in circumferential wall tension (CWT) is an important determinant of vascular remodeling during hypertension or arteriosclerosis but also arteriogenesis. Although pivotal for such processes, the effect of this biomechanical force on venous remodeling has not yet been delineated. To this end, we raised the filling pressure in veins of the mouse auricle, which led to a 2.5-fold enlargement of these blood vessels within 4 d along with an increase in smooth muscle cell proliferation, matrix metalloproteinase 2 (MMP-2) expression and gelatinase activity. These changes were likewise observed in tissue samples of human varicose veins. Topical treatment of the auricles with a decoy oligonucleotide-neutralizing activator protein 1 (AP-1) inhibited these effects. Likewise, proliferation, MMP-2 expression, and gelatinase activity in both native and cultured venous smooth muscle cells exposed to enhanced stretch was decreased by up to 80% through inhibiting AP-1. In contrast, mutant control oligonucleotides had no effect on smooth muscle cell activation. These findings indicate that an increase in venous filling pressure and thus CWT is sufficient to activate AP-1, which, in turn, triggers varicose remodeling through fuelling MMP-2 activity and smooth muscle cell hyperplasia in the venous vessel wall.
Gesehen am 05.05.2022